Statistical analysis of weekly rainfall - IYENGAR , RNARAYANA (MAUSAM, 1987)
This paper presents a statistical analysis of weekly rainfall at eight stations in Karnataka. Apart from the usual mean and standard deviations, the power spectral density functions are computed. It is found that the rainfall at Mangalore shows a dominant period of about 40 days. Further it is found that some stations show significant week to week dependence.